In the Intermissions: Collected Works on Research into the Essentials of Theoretical Physics - A. Trutnev Yu (World Scientific, 1998)
This text offers an account of the creative work of theorists at the largest Soviet secret laboratory, now the Russian Federal Nuclear Center at Arzamas-16, and concrete situations where some famous results on the essentials of theoretical physics emerged in the intermissions of the quest for bombs. The collection contains about 30 papers with brief comments.